2014
DOI: 10.1016/j.neuron.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Switch of the Axon Guidance Receptor Robo3 during Vertebrate Evolution

Abstract: Development of neuronal circuits is controlled by evolutionarily conserved axon guidance molecules, including Slits, the repulsive ligands for roundabout (Robo) receptors, and Netrin-1, which mediates attraction through the DCC receptor. We discovered that the Robo3 receptor fundamentally changed its mechanism of action during mammalian evolution. Unlike other Robo receptors, mammalian Robo3 is not a high-affinity receptor for Slits because of specific substitutions in the first immunoglobulin domain. Instead,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
203
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(205 citation statements)
references
References 75 publications
2
203
0
Order By: Relevance
“…It is likely to be that all signalling pathways influencing commissural guidance integrate either directly or indirectly at some molecular level 45 . However, as we and others have demonstrated that Ntn-1, Dcc, Robo3 and Boc mutant embryos have different neuronal phenotypes, this strongly supports partial non-overlapping functions of different genes in commissural guidance.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely to be that all signalling pathways influencing commissural guidance integrate either directly or indirectly at some molecular level 45 . However, as we and others have demonstrated that Ntn-1, Dcc, Robo3 and Boc mutant embryos have different neuronal phenotypes, this strongly supports partial non-overlapping functions of different genes in commissural guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Heparan sulfate proteoglycans can also bind to both Slit and Robo, forming a ternary complex and stabilizing their interaction at the membrane (Hohenester, 2008;Morlot et al, 2007;Zelina et al, 2014;Zhang et al, 2013). Slits can also homodimerize; the LRR4 domain is required for this dimerization (Seiradake et al, 2009).…”
Section: Slit Ligands and Robo Receptorsmentioning
confidence: 99%
“…More recently, it was shown that, due to a few amino acid changes in its Ig1 domain, mammalian Robo3 has lost the ability to bind Slits (Zelina et al, 2014). Concomitantly, Robo3 has acquired new signaling properties, exhibiting interactions with the netrin 1/Dcc chemoattractive signaling pathway.…”
Section: The Proteolytic Processing Of Robo and Slitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Function blocking antibodies against P-cadherin reduced the secretion of Slit2 by oral epithelia, as well as reduced P-cadherin/Robo3 complex formation (Bauer et al 2011). Complicating matters, a recent study investigating the divergent roles of Robo3 compared to other Robo family members, revealed that Robo3 does not bind tightly to Slit proteins (Zelina et al 2014). Instead, the secreted factor NELL2 is the high-affinity ligand for Robo3 (Jaworski et al 2015).…”
Section: Slit-robo Regulation Of Adherens Junctionsmentioning
confidence: 99%